EFFICIENCY ANALYSIS OF SMALLHOLDER PALM OIL PLANTATIONS IN INDONESIA: IMPLICATIONS FOR SUSTAINABLE RESOURCE MANAGEMENT - Anggara, Rizki Tri; Alfahma, Elsya Gumayanti (Department of Economics, Faculty of Economics and Business, Universitas Brawijaya, 2025)
Purpose This study examines the palm oil plantation in Indonesia, highlighting its economic significance alongside its concerning ties to deforestation and biodiversity loss, with a particular focus on assessing the industry's land use efficiency. Design/methodology/approach The analysis focuses on the smallholder industry in Indonesia's top ten palm oil-producing provinces, using 2021 data from the Ministry of Agriculture and employs Data Envelopment Analysis (DEA). Findings This study has identified varying levels of land use effectiveness in Indonesian smallholder palm oil producers across several provinces. The findings suggest opportunities for enhanced land management in Riau, West Kalimantan, Jambi, Central Kalimantan, and East Kalimantan Province. Research limitations/implications The findings have implications for addressing deforestation and optimizing efficiency in palm oil plantations. It suggests implementing focused policy interventions to maximize resource utilization instead of expanding plantation lands further. Originality/value This research focuses on land use inefficiencies as a key variable to address this gap.